Research Progress on Supported Metal Catalysts for Thermal Catalytic Oxidation of 5-Hydroxymethylfurfural to 2,5-Furan Dicarboxylic Acid - Wang, Yanxing; Xiong, Lian; Chen, Xuefang; Li, Hailong; Zhang, Hairong; Peng, Fen; Chen, Xinde (The Korean journal of chemical engineering, 2025)
Biomass resources have become a research hotspot in the field of chemical industry to explore new resources because of its abundant total amount and wide distribution range. Biomass-based 2,5-furanediformic acid (FDCA) has attracted much attention due to its potential as a substitute for petroleum-based terephthalic acid (PTA), which industrial production can protect the environment and save resources. 5-Hydroxymethylfurfural (HMF) is a representative biomass-based platform compound with a wide range of raw materials and a green and sustainable preparation process. Hence, the preparation of FDCA from HMF has attracted much attention in recent years. In this review, HMF oxidation reaction pathway and different catalysts and carriers are reviewed, chiefly including noble metal catalysts, non-noble metal catalysts, metal oxide carriers, non-metal oxide carriers, resin carriers, and other carriers. In particular, the great industrial application potential of the resin carriers loaded with noble metals. We have tentatively prepared an efficient catalyst for the oxidation of HMF to FDCA using macroporous resins loaded with noble metals. Finally, the industrial application of resin-supported noble metal catalysts in the preparation of FDCA by HMF is summarized and prospected. This paper focuses on the research progress of conversion of HMF to FDCA by thermal catalysis, summarizes the research achievements and exists problems of catalytic oxidation of HMF to prepare FDCA, points out the factors limiting the industrialization of HMF to FDCA, and discusses the possible solutions. Finally, the research direction is provided for the industrialization of HMF to FDCA in future.